2011
DOI: 10.5604/15093492.967222
|View full text |Cite
|
Sign up to set email alerts
|

Problems and complications in VEPTR-based treatment.

Abstract: STRESZCZEnIEWstep. Sko lio zy wcze sno dzie cię ce z to wa rzy szą cy mi de for ma cja mi klat ki pier sio wej są wy jąt ko wo trud nym pro blemem lecz ni czym. Wcze sne le cze nie ope ra cyj ne jest za zwy czaj je dy nym ra cjo nal nym roz wią za niem. Wy ko rzy stu je się tech ni ki umo żli wia ją ce ta ką ko rek cję krę go słu pa i klat ki pier sio wej, któ ra za pew nił by ich dal szy wzrost. Jed nym ze sposo bów na pra wy jest za sto so wa nie sys te mu VEPTR (pio no we roz su wal ne że bro ty ta no we) z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Despite the previously proposed benefits of the VEPTR device, recent literature suggests that serious problems may be associated with this treatment method and long-term outcomes may be less optimistic than those reported in the earlier literature [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the previously proposed benefits of the VEPTR device, recent literature suggests that serious problems may be associated with this treatment method and long-term outcomes may be less optimistic than those reported in the earlier literature [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Ramirez et al 18 reported a complication rate of 13%, consisting of infection, device migration, and rib fracture. 21,30, 31 Betz and colleagues reported on a cohort of 43 patients with Jeune or Jarcho-Levin syndromes, in which there was a 9% mortality rate due to nondevice complications and another 9% had life-threatening complications including necrotizing entercolitis, acute respiratory distress syndrome, cardiac arrest after central line insertion, and meperidine overdose. 15 A number of smaller, single-center series have also experienced similar complications.…”
Section: Discussionmentioning
confidence: 99%
“…1,[3][4][5][6][7][8][9][10][11] Anterior spinal approaches require thoracotomies, laparotomies, lumbotomies, etc., all of which offer broad exposure but also severe injury to the adjacent tissues with undesirable, and sometimes definitive, secondary effects. [12][13][14][15] It is important to achieve outcomes similar to those of conventional surgery without most of its inconveniences of unnecessary damage to adjacent tissues. This is why the benefits obtained from minimally invasive techniques are not limited only to the size of the incision, but also to a less painful postoperative period and the possibility for the patient to return more rapidly to their day-to-day life.…”
Section: Introductionmentioning
confidence: 99%